Teachers’ perspective on active methodologies: demands for the use of the case method in chemistry teaching (Research, Society and Development, 2022)
The article presents research aimed at identifying the knowledge, use and expectations of professors from a federal educational institution in relation to active methodologies (AMs), specifically the case method. This analysis can help organize continuing education activities for teachers, aiming to encourage the use of AMs in chemistry teaching. With a qualitative approach and descriptive objective, it presents a case study with the application of a questionnaire sent to the sixteen participating teachers from the google forms platform, containing nineteen questions divided into two blocks: (i) one block presents nine questions that helped to identify and to trace the academic and professional profile of the participants, and (ii) another block containing ten questions that allowed mapping the knowledge, training, interest and experience of teachers in relation to the use of AMs in teaching chemistry. The analysis of the responses indicates a lack of knowledge of most of the participating teachers in relation to the topic, which does not encourage them to use these teaching resources in the classroom. Therefore, there is a demand for the development of teaching material aimed at continuing education courses for teachers, aiming to encourage the use of these AMs in the teaching of chemistry.